Morphological and molecular analysis reveal a new species in the genus Leptobacillium (Cordycipitaceae, Hypocreales) isolated from Camellia oleifera rhizosphere - Chang, Xiao-Yun; Hu, Jiang-Xin; Shen, Dan-Qi; Han, Yi-Ren; Liu, Yu-Jun; Huang, Bo; Chen, Ming-Jun (Phytotaxa, 2024)
The investigation of fungal diversity in the rhizosphere of Camellia oleifera led to the isolation of two saprophytic fungal strains from the Xianyu Mountains, Anhui Province, China. Morphologically, these strains exhibited an irregular colony surface with divergent cracks, along with predominantly solitary slender phialides that produced narrow cylindrical conidia in chains. To further elucidate their taxonomic position, phylogenetic analyses were conducted using ITS and LSU rDNA region sequences, employing maximum-likelihood and Bayesian inference. The results unequivocally supported that these isolated strains belong to the genus Leptobacillium and represent a previously undescribed species. Consequently, based on their discernible morphological and phylogenetic characteristics in comparison to other Leptobacillium species, we propose a new fungal taxon, L. xianyushanense sp. nov.